Conceptual framework for temporal discontinuance experiences of social media users: What factors are responsible?. (February 2023) - Franks, Jessica; Chenhall, Richard; Keogh, Louise
Temporarily disconnecting from social media has become more widespread in recent years with users choosing to limit or stop engaging with social media platforms for a period of time. There are no published syntheses that integrate the collective research on this phenomenon, nor how this behaviour is experienced. This review provides insight into the research on this phenomenon and proposes a conceptual framework for understanding social media user's temporal discontinuance experience. We conducted a scoping review of 27 articles published during 2010–2020, focusing on the most salient factors of temporal discontinuance. Our review revealed a number of issues related to users' motivations for temporal discontinuance, including the need to address self-reported problematic and excessive social media use, the want to restore control and/or agency, as well as the desire to minimise distractions and address privacy concerns. We identified the various benefits and challenges temporal disconnectors experience and describe two specific practices related to their return to social media use: 1) manipulating technological and/or platform affordances and/or 2) self-regulating behaviours. The paper concludes with suggestions for future research.